Upaya Meningkatkan Hasil Belajar Matematika Materi Diagram Batang melalui Model Pembelajaran Problem Based Learning pada Siswa Kelas IV SDN Sidodadi II No 579 - Puput Della Fitriani; Delia Indrawati; Amie Amie (Journal on Education, 2023)
The learning process experienced by students shows changes in the affective domain which is expressed by attitudes and in the cognitive domain which is expressed by values, as well as the psychomotor aspect which indicates the success of learning activities. Factors that influence learning outcomes include the use of learning models that are appropriate and relevant to the lives of students. The purpose of this study was to determine the application of the PBL (Problem Based Learning) learning model in mathematics subject matter of bar chart data presentation. The study used the Classroom Action Research method which consisted of 3 cycles, namely cycle 1, cycle 2, and cycle 3. The learning activities of students in cycle 1 were classified as quite active with a percentage of learning outcomes of 80.74, in cycle 2 they experienced the increase is in the active category with a percentage of learning outcomes of 87.40, and in cycle 3 it has increased, namely in the very good and active category with a percentage of learning outcomes of 94.07. The conclusion from this study, the use of the Problem Based Learning (PBL) model in mathematics, bar chart data presentation material in class IV SDN Sidodadi II No 579 can increase student activity and learning outcomes.